B ANALISIS USAHATANI PADI SAWAH DI DESA KOMBA-KOMBA KECAMATAN KABANGKA KABUPATEN MUNA - Basri Sufa (Fakultas Pertanian Universitas Muhammadiyah kendari, 2023)
This study aims to determine what factors influence the production of lowland rice farming and to determine the amount of farmers' income in lowland rice farming in Komba Komba Village, Kabangka District, Muna Regency. The method of determining the sample in this study was carried out by census on 34 farmers who carry out agricultural land utilization activities as paddy rice farming in Komba-Kamba Village. Data collection was carried out by means of observation, interviews, documentation and using a questionnaire. The data analysis used in this study is the Cobb-Douglas function and income. The results of this study show that the simultaneous regression coefficient test results indicate that the estimated regression model is feasible to be used to explain the effect of production factors on paddy rice farming production simultaneously and the partial regression coefficient test results indicate that the factors influencing lowland rice farming production in Komba-Komba Village, Kabangka District, Muna Regency are the variables of fertilizer, labor, and land area, each of which has a significance value (sig.) < Production, Revenue, cobb-douglas